Strategi Pembelajaran Berbasis Teori Memori untuk Peningkatan Kognitif Siswa: Strategi Pembelajaran Berbasis Teori Memori untuk Peningkatan Kognitif Siswa - Zainuri, Siti Machmudah; Siti Machmudah Zainuri; Muinuddin (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
This article examines the mechanism of memory with a focus on three main components, namely information processing, storage, and information recall. Memory is a crucial cognitive element in enabling individuals to process, store, and access the information needed in various activities. Information processing includes the initial stage where the received information is encoded in order to be stored in a memory system. Information storage is divided into three types, namely sensory, short-term, and long-term memory, each of which has a different capacity and duration in retaining information. Information recall involves re-access to information that has been stored, and is influenced by various factors such as context, signals, and emotional states. Through a literature research approach, this article outlines the key theories in memory studies, and highlights how a deep understanding of memory processes can be applied in education to improve learning effectiveness